2022
DOI: 10.3390/ncrna8060072
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Its Modulation by Ladostigil Alter the Expression of Abundant Long Non-Coding RNAs in SH-SY5Y Cells

Abstract: Neurodegenerative disorders, brain injury, and the decline in cognitive function with aging are accompanied by a reduced capacity of cells in the brain to cope with oxidative stress and inflammation. In this study, we focused on the response to oxidative stress in SH-SY5Y, a human neuroblastoma cell line. We monitored the viability of the cells in the presence of oxidative stress. Such stress was induced by hydrogen peroxide or by Sin1 (3-morpholinosydnonimine) that generates reactive oxygen and nitrogen speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 92 publications
(115 reference statements)
0
0
0
Order By: Relevance
“…HDLBP was significantly upregulated in HCC tissues and this upregulation inhibited ferroptosis through stabilizing cytoplasmic ferroptosis-associated lncRNA (lncFAL) [ 131 ]. LncFAL decreased ferroptosis susceptibility through disrupting the ferroptosis suppressor protein 1 (FSP1)-TRIM69 interaction and competitively inhibiting the polyubiquitination and degradation of FSP1 [ 132 ]. These results advocate the considerable potential of targeting FSP1 as a promising therapeutic approach for HCC patients exhibiting upregulated expression of HDLBP or lncFAL, which also implies that targeting ferroptosis-suppressive lncRNAs could offer a novel therapeutic approach for HCC patients.…”
Section: Ferroptosis-related Lncrnas In Hcc Progression and Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…HDLBP was significantly upregulated in HCC tissues and this upregulation inhibited ferroptosis through stabilizing cytoplasmic ferroptosis-associated lncRNA (lncFAL) [ 131 ]. LncFAL decreased ferroptosis susceptibility through disrupting the ferroptosis suppressor protein 1 (FSP1)-TRIM69 interaction and competitively inhibiting the polyubiquitination and degradation of FSP1 [ 132 ]. These results advocate the considerable potential of targeting FSP1 as a promising therapeutic approach for HCC patients exhibiting upregulated expression of HDLBP or lncFAL, which also implies that targeting ferroptosis-suppressive lncRNAs could offer a novel therapeutic approach for HCC patients.…”
Section: Ferroptosis-related Lncrnas In Hcc Progression and Prognosismentioning
confidence: 99%
“…The lncRNA GABPB1-AS1 is the antisense transcript of GABPB1 mRNA [ 139 ]. The expression of GABPB1-AS1 might fluctuate in response to stress stimuli [ 132 , 140 ]. Qi et al [ 140 ] have revealed that erastin activated the transcription of GABPB1-AS1, which significantly reduced the expression of GABPB1, resulting in decreased PRDX5 peroxidase expression.…”
Section: Ferroptosis-related Lncrnas In Hcc Progression and Prognosismentioning
confidence: 99%
“…This prodrug has been shown to inhibit both AChE and BuChE, which, by decarbamylating this molecule, releases a phenol derivative of rasagiline, a monoamine oxidase B inhibitor (MAO-B), which is also used in Parkinson's disease for its neuroprotective effect. Ladostigil has been involved in clinical trials against Alzheimer's disease and has led to the synthesis of numerous analogues [26][27][28]. Furthermore, based on the same principle, other pleiotropic prodrugs have been designed by exploiting cholinesterase inhibition to release various phenolic drugs, such as hydroxyquinoline with metal-chelator and Aβ inhibitory properties [29] or an indole derivative with 5-HT 6 R-antagonist properties [30].…”
Section: Pleiotropic Structural Compromisesmentioning
confidence: 99%